PENGEMBANGAN MEDIA BIG BOOK MENGGUNAKAN KAIN PERCA PADA TEMA BENDA, HEWAN DAN TANAMAN DI SEKITARKU SISWA KELAS I SD - Pratiwi, Dewi; Sujarwo (PGSD UMN Al-Washliyah, 2023)
This research is entitled Development of Big Book Media Using Patchwork on the Themes of Objects, Animals, and Plants Around Me. This research is motivated by the low interest in student learning and the absence of Big Book media development. This study aims to describe: (1) Development of Big Book media in integrated thematic learning for grade I SD (2) Improve student learning outcomes by using Big Book media on learning animals around me for grade I SD Muhammadiyah 19 Medan. This type of research is Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The sample used is 11 students and uses a research instrument in the form of a questionnaire. This study proves that: 1) Big book media development scored 83.3% in the very feasible category by material experts, media experts scored 92.8% in the very feasible category and in the teacher's response a score of 97.3% is in the very decent category. 2) Product effectiveness is carried out by conducting pretest and posttest, so there are differences in results before and after using big book media so that there is an increase in the average score of students from 61.81 to 85.45. It can be concluded that Big Book media is in the very effective category. . 3) At the qualification level of validity, the score of 83.3% is in the valid category by material experts, the media expert gets a score of 92.8% is in the very valid category, and in the teacher's response, the score is 97.3% is in the very valid category.